Availability and Quantity of Human and Material Resources of Nigerian Universities' HIV Youth Friendly Centres: Implication for Policy Implementation - A.G. Akintomide; O.O. Ojo (University of Sofia, 2017)
The study assessed the availability and quality of human and material resources at the Campus-based Youth Friendly Centres in Southwestern Nigeria. The survey research design was adopted and the study was carried out among ten counsellors and centre coordinators of Youth Friendly Centres in four higher institutions of learning in Southwest Nigeria using interview guide and observation checklist to collect data. The result revealed that there were no enough counsellors at the YFCs and some of the counsellors available at the centres did not have enough qualification to render HIV counselling. It was also revealed that material resources were moderately available at most of the centres but not up to the require standard stipulated by the World Health Organization.